G370(P) Fictitious illness due to chronic laxative poisoning: a case report. (27th April 2015) - Atukorale, DC; Jayatunga, R
Abstract : Aims: Fictitious Illness is a form of child abuse, where a perpetrator makes a child appear sick by either fabricating symptoms or actually causing harm to the child, in order to gain attention. The child could be poisoned by the perpetrator to induce the symptoms. Method: We report the course of a girl who presented with chronic diarrhoea and severe failure to thrive, as a result of chronic laxative poisoning, by her mother. A review of the English literature (PubMed) revealed only 1 other similar case report in an infant. Results: A girl was admitted repeatedly (11 admissions in 11 months) to hospital between the ages of 3 weeks and 11 months for further evaluation of chronic diarrhoea and severe growth faltering. Her mother reported that she had vomiting, poor feeding and diarrhoea. Her birth weight was 4.07 kg (91 st centile) but at 11 months she was emaciated, weighing only 6.94 kg (well below the 3 rd centile). She had been extensively investigated for a cause, including regular blood, stool and urine tests, imaging and intestinal biopsies. As the aetiology for her symptoms was not found, she was managed for possible gastro-oesophagial reflux and cow's milk protein intolerance, although neither were proven. But her symptoms continued, despite a multi-disciplinary approach from paediatricians, tertiary gastroenterologists, dieticians, community nursing and health visitor, causing significant malnutrition and delayed development, by 1 year of age. Incidental finding of Bisacodyl with the child's belongings during an admission led to the suspicion of laxative poisoning. It was confirmed with positive urine toxicology for Bisacodyl on two separate occasions. Mother was removed from the care of the child with involvement of social services. Following this, she made excellent progress and her weight increased from 6.925 kg to 9.35 kg within a period of 3 ½ weeks giving an average weight gain of 692 g per week. In foster care her development returned to normality. Conclusions: We highlight the need to consider this rare diagnosis when extensive investigations fail to identify an underlying cause in infants with severe weight loss due to protracted diarrhoea.